To find the equation of a line in slope-intercept form (y = mx + b), we need to find the slope (m) and the y-intercept (b).
Given the coordinates (3, 0) and (0, -2), we can calculate the slope (m) using the formula: m = (y2 - y1) / (x2 - x1)
Using (3, 0) as (x1, y1) and (0, -2) as (x2, y2):
m = (-2 - 0) / (0 - 3)
m = -2 / -3
m = 2/3
Therefore, the slope (m) is 2/3.
We also know that the line passes through the positive 3 on the x-axis. This means that the line will have a y-intercept of 0, as it crosses the y-axis at the point (0, 0).
Now, we can write the equation of the line in slope-intercept form:
y = mx + b
Substituting the slope (m) as 2/3 and the y-intercept (b) as 0, the equation becomes:
y = (2/3)x + 0
Simplifying, the equation of the line is:
y = (2/3)x
write the equation of the line in slope-intercept form. the coordinates are (3, 0) and (0, -2) and the line passes through the positive 3 on the x-axis.
7 answers
thats wrong
I apologize for the error. Let's correct it:
To find the equation of the line in slope-intercept form (y = mx + b), we need to find the slope (m) and the y-intercept (b).
Given the coordinates (3, 0) and (0, -2), we can calculate the slope (m) using the formula: m = (y2 - y1) / (x2 - x1)
Using (3, 0) as (x1, y1) and (0, -2) as (x2, y2):
m = (-2 - 0) / (0 - 3)
m = -2 / -3
m = 2/3
Therefore, the slope (m) is 2/3.
Now, to find the y-intercept (b), we know that the line passes through the positive 3 on the x-axis. This means that when x = 3, y = 0.
We can substitute these values in the slope-intercept form equation to find b:
0 = (2/3)(3) + b
0 = 2 + b
b = -2
Therefore, the y-intercept (b) is -2.
Now, we can write the equation of the line in slope-intercept form:
y = mx + b
Substituting the slope (m) as 2/3 and the y-intercept (b) as -2, the equation becomes:
y = (2/3)x - 2
Thus, the corrected equation of the line in slope-intercept form is y = (2/3)x - 2.
To find the equation of the line in slope-intercept form (y = mx + b), we need to find the slope (m) and the y-intercept (b).
Given the coordinates (3, 0) and (0, -2), we can calculate the slope (m) using the formula: m = (y2 - y1) / (x2 - x1)
Using (3, 0) as (x1, y1) and (0, -2) as (x2, y2):
m = (-2 - 0) / (0 - 3)
m = -2 / -3
m = 2/3
Therefore, the slope (m) is 2/3.
Now, to find the y-intercept (b), we know that the line passes through the positive 3 on the x-axis. This means that when x = 3, y = 0.
We can substitute these values in the slope-intercept form equation to find b:
0 = (2/3)(3) + b
0 = 2 + b
b = -2
Therefore, the y-intercept (b) is -2.
Now, we can write the equation of the line in slope-intercept form:
y = mx + b
Substituting the slope (m) as 2/3 and the y-intercept (b) as -2, the equation becomes:
y = (2/3)x - 2
Thus, the corrected equation of the line in slope-intercept form is y = (2/3)x - 2.
given the equation y= -x+2, what is the slope? write your answer as an integer.
The slope of the equation y = -x + 2 is -1.
given the equation y=-2x+2, what is the slope? write your answer as an integer.
The slope of the equation y = -2x + 2 is -2.